Penyuluhan Kesehatan Tentang Premenstrual Syndrome - Novica Jolyarni; Nailatun Nadrah; Fitriyani Nasution; Aswin Syahputra (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2023)
Health education about Premenstrual Syndrome (PMS) aims to improve the understanding and awareness of adolescent girls at MTSN 1 Rantau Selatan regarding the symptoms, causes, and management of PMS. This research was conducted in January 2025 using an educational and interactive method, which included presentations, discussions, simulations, and distribution of educational materials. The results of the outreach showed a significant improvement in the participants' knowledge about PMS, as well as a positive shift in their attitudes toward the condition. Before the intervention, most participants were unaware of PMS symptoms and appropriate management strategies. After the session, they became more open to discussing menstruation-related issues and better equipped to manage PMS symptoms healthily. However, some participants still require ongoing support to implement techniques such as acupressure and light exercises. This program is expected to reduce stigma surrounding PMS and improve the reproductive health of adolescent girls at MTSN 1 Rantau Selatan.